Coil–rod–coil triblock copolymers synthesized by macromolecular clicking and their compatibilizer effects in all-polymer solar cells. Issue 1 (13th December 2021) - Otep, Sultan; Tseng, Yu-Cheng; Yomogita, Naomasa; Chang, Jia-Fu; Chueh, Chu-Chen; Michinobu, Tsuyoshi
Abstract : Macromolecular clicking of poly(arylenebutadiynylene)s produces excellent block copolymer-based compatibilizers for all-polymer solar cells. Abstract : Poly(diethynylthiophene) (PDET ) synthesized via Hay coupling polycondensation retains terminal alkynes for tethering polystyrene (PS) blocks by a simple Cu-catalyzed azide–alkyne click (CuAAC) reaction. The successful synthesis of triblock copolymers was confirmed by 1 H NMR, FTIR, and GPC measurements. Optical and electrochemical properties of the PDET block were conserved in the triblock copolymers, as determined from the UV-vis absorption spectra and redox potentials. Surface topography of the polymer films revealed the micrometer-scale features attributable to phase separation, which was supported by thermal analyses. The compatibilizer functions of PDET and triblock copolymer P1 were investigated and compared in all-polymer solar cells (all-PSCs). Addition of 1 wt% P1 was shown to result in an enhanced power conversion efficiency (PCE) from 5.90% to 6.24%, corresponding to a relative increase of ∼6%, whereas the addition of 1 wt% PDET decreased the resultant PCE. Notably, adding a proper compatibilizer helped reduce the device's potential loss, as evidenced by the improved V oc in the 1 wt% P1 device. Our results highlight the critical role of the coil segment in designing block copolymer-based compatibilizers for all-PSCs. Also, this study demonstrates a straightforward synthetic route for coil–rod–coil triblock copolymers that afford a compatibilizer function suitable for all-PSCs.